A possible decline in the incidence and severity of Behçet's disease: implications for an infectious etiology and oral health - (:unkn) unknown (My University, 2010)
Behçet's disease (BD) is a systemic and inflammatory disorder mainly present along the ancient Silk Road, from the Mediterranean to East Asia. A wide range of prevalence figures (0.1-420/100.000) are reported for BD, also among populations of similar ethnicity living in different countries. Recently, a decline of the incidence of BD and a change of the disease spectrum to less severe mucocutaneous manifestations is reported from Japan, a genetically homogenous, affluent population with limited immigration. Among environmental factors, a change in atopy/allergic disorders and a decline in infections are two possible mechanisms for this epidemiological change. A shift in Th1/Th2 immune balance towards Th2-associated immune responses are possible, however 'hygiene hypothesis' associated with this approach does not explain the recent trend of the increase in Th1-associated disorders such as inflammatory bowel disease and multiple sclerosis in Western Countries. We hypothesise that a decline in oral infections, associated with the improvement in oral health in Japan, could be behind this decline. Better epidemiological studies in other populations will show whether this decline is a worldwide trend and may provide a better understanding of the environmental factors associated with the onset or relapses of BD, leading a way to new therapeutic approaches.
Keywords: Humans; Behcet Syndrome; Turkey; Oral Health; Europe; Severity of Illness Index; Incidence; Japan; Mouth Diseases